1996
DOI: 10.1097/00005768-199612000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise and vitamin C on absorption of ferric sodium citrate

Abstract: The effect of physical exercise and vitamin C on iron absorption after oral iron administration was investigated. Eight healthy male subjects without iron deficiency were studied after administration of 100 mg ferric sodium citrate complex, 100 mg ferric sodium citrate complex with 200 mg ascorbic acid, and without iron intake, both under resting conditions and after a 1-h bicycle ergometer test at moderate exercise. Serum concentrations for iron, transferrin, and ferritin were measured before and 30 min, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Although exact mechanisms of dissolving iron nanoparticles by SC were not investigated in this study, there have been reports showing that citrates have a greater affinity for ferric iron (Fe[III]) than ferrous iron (Fe [II]) and facilitate absorption of iron. 30,31 Dicarboxylic acids, such as citrate, form a more stable complex with transferrin and ferric iron. 32 In the current study, it can be concluded that both the presence of chelates (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although exact mechanisms of dissolving iron nanoparticles by SC were not investigated in this study, there have been reports showing that citrates have a greater affinity for ferric iron (Fe[III]) than ferrous iron (Fe [II]) and facilitate absorption of iron. 30,31 Dicarboxylic acids, such as citrate, form a more stable complex with transferrin and ferric iron. 32 In the current study, it can be concluded that both the presence of chelates (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Iron excretion through sweat, urine and faeces is believed to be increased from normal levels, although contrasting evidence has also been presented (see earlier in this review). In contrast, iron absorption may be slightly improved by physical activity 35,88 .…”
Section: Minerals and Trace Elementsmentioning
confidence: 99%
“…18 Fiziksel egzersiz sırasında da kan Fe ++ düzeyinin C vit aracılığıyla yükseldiği gösterilmiştir. 19 Arslan ve ark. 20 yaptığı bir çalışmada, kız atletlerin Fe ++ düzeyleri spor yapmayan kontrollere oranla düşük, TDBK ise yüksek bulunmuştur.…”
Section: Discussionunclassified